The WONCA Europe 2016 Family Medicine Conference was Held in Copenhagen - Esra Meltem Koç (Family Practice and Palliative Care, 2016)
WONCA Europe 2016 organized by the World Organization of Family Doctors was held in Copenhagen, the capital city of Denmark, between 15 and 18 June 2016. Many European countries participated in the congress.WONCA Europe 2016 was organized with the theme “Family Doctors with Heads and Hearts” and calls for action to achieve:ü  Global health insurance, high quality family medicine practices throughout Europe and further development of family medicineü  integration of healthcare services across different healthcare professionals at the primary care level, as well as across primary and secondary care.ü  stronger links between public health strategies and person-oriented medicine in clinical practice.ü  a rational distribution of resources driven by the needs of the community. More than 3000 family physicians from different countries participated in the conference. More than 600 poster and 800 non-poster presentations (oral presentations, workshops and symposiums) were performed. Nearly a group of 60 participants included academics, family medicine specialists and residents from Turkey and this group from Turkey demonstrated significant scientific participation with oral presentations, poster presentations and workshops.Activities conducted by special interest groups and networks on various subjects played an important role in providing content. The symposiums and workshops held by special interest groups and networks focused on “Aging in Europe, optimizing healthcare services, the future of family medicine, a vital task for family medicine: diagnosis, inequalities in special patient groups and healthcare”. Meetings were held about refugees and refugee health that has gained importance throughout the world lately. Additionally, doctors participating from our country shared their experience in different fields with their European colleagues and new joint research groups were formed for multicentric studies.The WONCA World Conference 2016 will be held in Rio, the WONCA Europe Conference 2017 will be held in Prague, 2018 will be in Krakow and 2019 will be in Bratislava.